Self-Recognition Sensitizes Mouse and Human Regulatory T Cells to Low-Dose CD28 Superagonist Stimulation - Langenhorst, Daniela; Tabares, Paula; Gulde, Tobias; Becklund, Bryan R.; Berr, Susanne; Surh, Charles D.; Beyersdorf, Niklas; Hünig, Thomas (Frontiers in Immunology, 2018)
In rodents, low doses of CD28-specific superagonistic monoclonal antibodies (CD28 superagonists, CD28SA) selectively activate regulatory T cells (Treg). This observation has recently been extended to humans, suggesting an option for the treatment of autoimmune and inflammatory diseases. A mechanistic explanation for this phenomenon is, however, still lacking. Given that CD28SA amplify T cell receptor (TCR) signals, we tested the hypothesis that the weak tonic TCR signals received by conventional CD4 T cells (Tconv) in the absence of cognate antigen require more CD28 signaling input for full activation than the stronger TCR signals received by self-reactive Treg. We report that in vitro, the response of mouse Treg and Tconv to CD28SA strongly depend on MHC class II expression by antigen presenting cells. To separate the effect of tonic TCR signals from self-peptide recognition, we compared the response of wildtype Treg and Tconv to low and high CD28SA doses upon transfer into wildtype or H-2M knockout mice, which lack a self-peptide repertoire. We found that the superior response of Treg to low CD28SA doses was lost in the absence of self-peptide presentation. We also tested if potentially pathogenic autoreactive Tconv would benefit from self-recognition induced sensitivity to CD28SA stimulation by transferring TCR transgenic OVA-specific Tconv into OVA-expressing mice, and found that low dose CD28SA application inhibited, rather than supported, their expansion, presumably due to the massive concomitant activation of Treg. Finally, we report that also in the in vitro response of human PBMC to CD28SA, HLA II blockade interferes with the expansion of Treg by low-dose CD28SA stimulation. These results provide a rational basis for the further development of low-dose CD28SA therapy for the improvement of Treg activity.